1992
DOI: 10.1007/bf02777723
|View full text |Cite
|
Sign up to set email alerts
|

The acrolein cytotoxicity and cytoprotective action of α-tocopherol

Abstract: The influence of acrolein on hepatocytes and the effect of alpha-tocopherol on acrolein cytotoxicity were investigated using primary cultured rat hepatocytes. Hepatocellular injury was dependent on both acrolein concentration in medium and on duration of exposure. Treatment of hepatocytes with 100 microM acrolein resulted in a marked loss of cellular glutathione (GSH) within 15 min, gradual accumulation of cellular lipid peroxide (LPO) and subsequent lactate dehydrogenase (LDH) leakage in the medium from 3 hr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These processes include apoptotic stress (caused by inhibition of nuclear factor kappa beta function in hepatocytes) and ER stress (as demonstrated in tunicamycin‐treated hepatocytes) . Other groups have shown that VitE inhibits hepatotoxicity . Ballooned hepatocytes, a hallmark of lipotoxicity in NASH, have been shown to exhibit apoptotic and ER stress .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes include apoptotic stress (caused by inhibition of nuclear factor kappa beta function in hepatocytes) and ER stress (as demonstrated in tunicamycin‐treated hepatocytes) . Other groups have shown that VitE inhibits hepatotoxicity . Ballooned hepatocytes, a hallmark of lipotoxicity in NASH, have been shown to exhibit apoptotic and ER stress .…”
Section: Discussionmentioning
confidence: 99%
“…14 Other groups have shown that VitE inhibits hepatotoxicity. [33][34][35][36] Ballooned hepatocytes, a hallmark of lipotoxicity in NASH, have been shown to exhibit apoptotic and ER stress. 12,37 NASH CRN data in humans with NASH enrolled in PIVENS demonstrated that VitE significantly reduced hepatocyte ballooning and serum ALT (a surrogate marker of hepatocyte injury).…”
Section: Discussionmentioning
confidence: 99%
“…Trolox -representing a water-soluble vitamin E derivative, 6-hydroxy-2,5,7,8-tetramethylchromane-2-carbonic acid -inhibits peroxynitrite-mediated oxidative stress (Salgo & Pryor, 1996), activates pregnane-X-receptor which regulates genes involved in xenobiotic detoxification (Traber, 2004), can protect from aldehyde toxicity (Watanabe et al, 1992), and has been demonstrated to inhibit apoptosis and to reduce cytotoxicity in various cell types, such as thymocytes and lymphocytes (Wu et al, 1990;McClain et al, 1995). Similarly, ascorbic acid has been demonstrated to inhibit peroxynitrite-induced apoptosis (Sandoval et al, 1997), to promote detoxification and elimination of 4-hydroxy-2(E)-nonenal (Miranda et al, 2009) and, together with N-acetylcystein, to protect against aldehyde toxicity (Sprince et al, 1975).…”
Section: Antioxidant Effects On Cp-induced Cytotoxicitymentioning
confidence: 99%